Comparison of 3D and 2D Li diffusion in cubic and hexagonal Li x TiS 2: a study by solid state 7 Li NMR methods - Wilkening, Martin; Heitjans, Paul (Diffusion Fundamentals, 2007)
Li diffusion in spinel-type structured cubic and hexagonal LixTiS2 with x = 0.6 and 0.7, respectively, was investigated by solid state NMR spectroscopy. In layered hexagonal LixTiS2, Li diffusion is known to be confined to the van-der-Waals gap between the TiS2 planes, i. e., it is two-dimensional (2D). In cubic LixTiS2, however, Li diffusion takes place in the three-dimensional (3D) interstitial space formed by the TiS6-polyhedra. Both polymorphs form a unique pair for studying the effects of dimensionality on Li diffusion within a host structure of the same chemical composition. 7Li spin-alignment echo and spin-lattice relaxation NMR methods were applied to measure Li jump rates. Additionally, solid echo NMR spectroscopy was used to estimate the Li diffusivity in cubic Li0.6TiS2. The activation energies for Li jumps in the two materials are very similar. Nevertheless, Li diffusion in the 3D host is slower than in the layered modification by a factor of about ten.